2021
DOI: 10.3390/ijms221910679
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Adult-Onset Asthma Related to Damp and Moldy Buildings and Idiopathic Environmental Intolerance

Abstract: A subset of adult-onset asthma patients attribute their symptoms to damp and moldy buildings. Symptoms of idiopathic environmental intolerance (IEI) may resemble asthma and these two entities overlap. We aimed to evaluate if a distinct clinical subtype of asthma related to damp and moldy buildings can be identified, to unravel its corresponding pathomechanistic gene signatures, and to investigate potential molecular similarities with IEI. Fifty female adult-onset asthma patients were categorized based on expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…), together with gene signatures of nasal biopsies and peripheral blood mononuclear cells. Overall, the results of this study revealed a greater degree of similarity between idiopathic environmental intolerance and dampness related asthma than between the same patients and those with asthma not associated to dampness and mold [16]. Transcriptome analysis revealed well defined pathological mechanisms for asthma without exposure to dampness, but not dampness-and-mold-related asthma patients.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…), together with gene signatures of nasal biopsies and peripheral blood mononuclear cells. Overall, the results of this study revealed a greater degree of similarity between idiopathic environmental intolerance and dampness related asthma than between the same patients and those with asthma not associated to dampness and mold [16]. Transcriptome analysis revealed well defined pathological mechanisms for asthma without exposure to dampness, but not dampness-and-mold-related asthma patients.…”
mentioning
confidence: 60%
“…Transcriptome analysis revealed well defined pathological mechanisms for asthma without exposure to dampness, but not dampness-and-mold-related asthma patients. Besides, a distinct molecular pathological profile in nasal and blood immune cells of idiopathic environmental intolerance subjects was found, including several differentially expressed genes (DEGs) that were also detected in dampness-and-mold-related asthma samples, thereby suggesting idiopathic environmental intolerance-type mechanisms [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In einigen Studien wird ein möglicher Zusammenhang zwischen Feuchte-/Schimmelbefall im Innenraum und MCS diskutiert [118,167,459,520,[548][549][550][551][552][553][554][555][556]. Vereinzelt wird auch von einem Dampness and Mold Hypersensitivity Syndrom [552,557] oder Toxic Mold Syndrome [459,558] gesprochen; letztes nicht ohne Widerspruch [456].…”
Section: Multiple Chemical Sensitivity (Syndrome) (Mcs)/idiopathic En...unclassified